NK1.1+ cells are important for the development of protective immunity against MHC I-deficient, HPV16-associated tumours - Indrová, Marie; Símová, Jana; Bieblová, Jana; Bubeník, Jan; Reinis, Milan (Oncology reports, 2011)
Loss or downregulation of MHC class I molecules on tumour cells is a common mechanism by which tumours can escape T-cell mediated immune responses. In this study, we examined the role of different immune cell lineages in the development of immunity against tumours of the same aetiology but with different MHC class I expression. In vivo depletion of CD8+ cells, but not of CD4+ or NK1.1+ cells in the immunization period resulted in complete elimination of the protective effects of immunization with irradiated TC-1 cells (MHC class I-positive cell line) against the TC-1 tumour challenge. After immunization with irradiated TC-1/A9 or with MK16 tumour cells (MHC class I-deficient sublines) a remarkable dependence on the presence of NK1.1+ cells was observed, while the tumour growth inhibition after CD4+ or CD8+ depletion was not efficient. Cytotoxic activity induced by TC-1 cell immunization was significantly abrogated in the CD8+ and CD4+ but not NK1.1+ cell-depleted mice, as compared to the immunized only controls. After MK16 or TC-1/A9 cell immunization, NK1.1+ but not CD8+ and CD4+ cell-depleted mice displayed significant reduction of specific cytotoxicity. Mice immunized with TC-1 cells showed similar percentage of IFNγ producing cells in CD8+, CD4+ and NK1.1+ cell populations. On the other hand, the highest proportion of IFNγ producing cells after immunization with TC-1/A9 or MK16 cells was concentrated into the NK1.1-positive spleen cell population. Our data demonstrate that the development of immunity against MHC class I-deficient tumours is highly dependent on the activity NK1.1+ cell population.
Keywords: Male; antigeny Ly; separace buněk; Cancer Vaccines; Histocompatibility Antigens Class I; Neoplasms, Experimental; mužské pohlaví; MHC antigeny I. třídy; CD8-Positive T-Lymphocytes; Flow Cytometry; Human papillomavirus 16; ELISA; lidský papilomavirus 16; NK Cell Lectin-Like Receptor Subfamily B; CD4-Positive T-Lymphocytes; Enzyme-Linked Immunosorbent Assay; průtoková cytometrie; Animals; experimentální nádory; CD8-pozitivní T-lymfocyty; Cell Separation; zvířata; lektinové receptory NK-buněk - podrodina B; buňky NK; Antigens, Ly; myši inbrední C57BL; protinádorové vakcíny; myši; Mice, Inbred C57BL; Mice; Killer Cells, Natural; CD4-pozitivní T-lymfocyty